MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN KERJASAMA PADA PEMBELAJARAN IPAS MENGGUNAKAN MODEL PROBLEM BASED LEARNING DENGAN MEDIA EDUBOX NUSANTARA DI KELAS V SDN KEBUN BUNGA 6 BANJARMASIN - Maharani, Adha; Nurhaliza, Maya; Chairani, Muhammad Alpian; Karim; Zulpah, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low levels of students critical thinking and collaboration skills in the Natural and Social Sciences subject among fifth-grade students at SDN Kebun Bunga 6 Banjarmasin. The purpose of this research was to improve students' critical thinking and collaboration skills through the implementation of the Problem Based Learning (PBL) model supported by EduBox Nusantara media. This study employed a Classroom Action Research (CAR) design conducted over three learning sessions. The results indicated that the success indicators for each aspect were achieved. The percentage of students' critical thinking skills reached 88%, while their collaboration skills reached 81%. Based on these findings, it can be concluded that the Problem Based Learning (PBL) model assisted by EduBox Nusantara media effectively improved the critical thinking and collaboration skills of fifth-grade students at SDN Kebun Bunga 6 Banjarmasin.